The relationship between respondents' characteristics to the incidence of hypertension in Baja Kuning Village, Tanjung Pura District - Icarestika Waluyani; Hilman Fauzi Harahap; Muhammad Aulia Fajri; Abdul Kholid Azhari; Tuti Anggraini (Universitas Ibn Khaldun Bogor, 2023)
The non-communicable disease with the greatest morbidity rate in Indonesian society is hypertension. Because the public frequently is unaware of this disease, the rise in incidence from year to year is highly concerning. An illness called hypertension is frequently experienced by elderly persons. The goal of this study was to determine how the prevalence of hypertension in Baja Kuning Village related to the characteristics of respondents based on age, gender, occupation, education, and history of hypertension. Cross-sectional study design using the Chi-Square statistical test and univariate and bivariate analysis are the methods employed. How to use a sphygmomanometer to assess hypertension by knocking on the doors of persons who are willing to have their blood pressure taken. According to the study's findings, there was a correlation between the characteristics of the respondents and the prevalence of hypertension based on age (p=0.001), gender (p=0.035), and previous hypertension (p=0.000). That is, there is a substantial correlation between the incidence of hypertension in Baja Kuning Village and the three variables. In Baja Kuning Village, Tanjung Pura District, the risk factor variables that cannot be adjusted tend to raise the risk of hypertension, according to the findings.